Structure of genetic diversity of Bemisia tabaci (Genn.) (Hemiptera: Aleyrodidae) populations in Brazilian crops and locations (Scientia Agricola, 2012)
Bemisia tabaci (Genn.) represents a complex of cryptic species that causes losses of many valuable crops. Even though there are differences in their ability to colonize hosts, transmit phytovirus and develop resistance to insecticides, the genetic differentiation of the insect populations is important for the adoption of control measures. Therefore, the genetic diversity of B. tabaci populations in economically important crops in Brazilian locations was characterized through a microsatellite analysis. Eight microsatellite markers were used for the analysis of eight populations, three in Solanum tuberosum (States of São Paulo, Minas Gerais and Bahia), two in Glycine max (States of São Paulo and Mato Grosso), one in Phaseolus vulgaris and Brassica oleracea var. acephala (States of São Paulo and Distrito Federal, respectively) and a cabbage population from Florida (USA). The number of alleles varied between two and 13 and the average value of F ST was 0.13. The population occurring in beans was genetically different, suggesting that the excessive use of insecticide or the host itself may have caused the modification of its allele frequency. The American population presented a large diversity and small differentiation compared to the Brazilian populations, especially from the Southeast, supporting the hypothesis that the B biotype was probably introduced into Brazil by the trade of plant material between the USA and the State of São Paulo. The genetic diversity found within and among the populations is geographically structured, and the insects from the central region of Brazil had superior genetic divergence when compared to the others Brazilian locations.